Analysis of Financial Literacy Level, Financial Behavior, and the Effect on Financial Planning Students in Medan City - Fadhila, Novi; Nainggolan, Edisah Putra; Hidayat, Rahmat (Journal of International Conference Proceedings, 2023)
Financial planning is the process of developing strategies and plans to manage one's or a family's finances, with the objective of achieving short and long-term financial stability. It involves identifying financial goals, assessing the current financial situation, and developing strategies to manage income, expenses, investments, and asset protection. This study aims to analyze the levels of financial literacy and financial behavior, and their influence on the financial planning of students in the city of Medan. The population for this study consisted of students from the State University in Medan City, with a sample size of 100 students. Quantitative analysis was conducted on the collected data using multiple linear regression analysis techniques. The research findings indicate that both the level of financial literacy and financial behavior have a partial and simultaneous influence on the financial planning of students in the city of Medan.